2016
DOI: 10.4314/ajcem.v17i3.4
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte subsets in prostate cancer subjects in south eastern Nigeria

Abstract: Humoral and cellular mechanisms play roles in immune response to foreign antigens. The present study was designed to determine the T lymphocyte subsets (CD4 + T cells, CD8 + T cells and CD4/CD8 ratio) in the prostate cancer subjects and control subjects. CD4 + T cells (µl/count) and CD8 + T cells (µl/count) were estimated using flow cytometric method by Partec while CD4/CD8 ratio was calculated from the results obtained from the CD4 + T cells and CD8 + T cells. CD4 + T cells and CD8 + T cells decreased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, in the same study, no significant difference was found between the CD4, CD8, and CD4/CD8 percentages of patients according to stage and presence of chemotherapy. 15 In our study, the percentages of lymphocyte subtype were examined in the peripheral blood sample of 137 patients with PCa, and the CD4+ T lymphocyte values were found to statistically significantly decrease with the increasing PSA value and pathological stage. The significant relationship between these parameters and CD4 T lymphocytes, which play a key role in the diagnosis, treatment, and follow-up of PCa, suggests that they can be used as important prognostic markers.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, in the same study, no significant difference was found between the CD4, CD8, and CD4/CD8 percentages of patients according to stage and presence of chemotherapy. 15 In our study, the percentages of lymphocyte subtype were examined in the peripheral blood sample of 137 patients with PCa, and the CD4+ T lymphocyte values were found to statistically significantly decrease with the increasing PSA value and pathological stage. The significant relationship between these parameters and CD4 T lymphocytes, which play a key role in the diagnosis, treatment, and follow-up of PCa, suggests that they can be used as important prognostic markers.…”
Section: Discussionmentioning
confidence: 78%
“…It was stated that CD4 T lymphocyte activity was lower in patients with advanced PCa compared to the healthy control group, and this was statistically significant. 14 In another study, in which 50 patients with PCa were evaluated in terms of lymphocyte subgroups, Oluboyo et al 15 detected a significant decrease in CD8 and CD4 T lymphocytes in peripheral blood in the PCa group compared to the healthy control group. However, in the same study, no significant difference was found between the CD4, CD8, and CD4/CD8 percentages of patients according to stage and presence of chemotherapy.…”
Section: Discussionmentioning
confidence: 97%